Performance study of organic based minimum quantity lubrication on machining difficult-to-cut material - Jamaludin, Ahmad Shahir; Razak, N. H.; Ibrahim, Ahmad Najmuddin; Osman Zahid, Muhammed Nafis; Rosli, Nurrina; Yusoff, A. R.; Amiril, S. A.S.; Razali, Mohd Nizar Mhd (2019)
Minimal Quantity Lubrication (MQL) is a method in machining that distributes a particular volume of lubrication to the tool tip by mixing with the desired amount of air and an oil aerosol. Thus, a study on properties that made an effective cutting fluid is needed, where the viscosity and density properties of the cutting fluids, mist size of the fluids and its relationship with the fluids viscosity will be observed. A cutting fluid that capable to act as a coolant or lubricant at the same time is particularly important for metalworking activity is designed through combination of vegetable oil and water. Along with that, the study also assesses the design of MQL nozzles with variable internal geometries and to investigate the relationship of MQL nozzle design with the effectiveness of MQL application in terms of MQL flow behavior. In this study, a few samples consisting of combination of oil, water and emulsion is mixed and studied. The percentage of emulsion is kept constant at 10% while the percentage of water is varied from 0%, 10%, 30% and 50%. The samples are prepared using a mixing machine in the laboratory. Then, a viscosity test is carried out followed by a mist particle spray test using a MQL mist sprayer and a microscope with Motic software. A simulation is also done to simulate, observe and analyse the flow of oil mist. Using simulation software ANSYS, the internal geometry of nozzle is designed to know the flow behavior of fluid when it through the nozzle under the same pressure and type of fluid. There are five types of internal geometry of nozzle which are 30o, 45o, 0o, -45o, and -30o. From the results of the viscosity test, it shows that the viscosity decreases with increase in percentage of water. The mist particle size proves to be larger when the viscosity is higher. Lastly, the simulation shows that the range of effectiveness of the Minimum Quantity Lubrication application is less than 20 mm away from the nozzle. The result obtained that the more effective nozzle when doing machining is by using the internal geometry 45o. The simulation results point out that the focusing-flow nozzle is more efficient nozzle in doing machining process using MQL method which is the internal geometry 45o is one of the focusing nozzle in this experiment. Besides, nozzle with internal geometry 45o has the oil mist shape of less disperse flow when flow out from the nozzle. It also has higher velocity of the oil mist flow. This study shows that, this flow behavior for internal geometry 45o more accurate to hit the cutting point and the tools that can cause faster cooling speed.